Rate of Pressure Ulcers in Intensive Units and General Wards of Iranian Hospitals and Methods for Their Detection. - Ali Akbari Sari; Leila Doshmanghir; Zahra Neghahban; Maryam Ghiasipour; Zeinab Beheshtizavareh (Tehran University of Medical Sciences, 2014)
This study aimed to estimate the rate of pressure ulcers in intensive care units (ICUs) and medical and surgical wards of Iranian hospitals and compare the performance of methods of medical record review as well as direct observation for their detection.The research team visited 308 patients in medical and surgical wards of hospitals affiliated with Tehran University of Medical Sciences and a further 90 patients in their ICUs between March 2009 and April 2010. In addition 310 patient records were randomly selected from patients discharged from the ICUs between March 2009 and April 2010. And a further 600 patient records were randomly selected from the patients that were discharged from medical and surgical wards between March 2010 and April 2011. These 910 selected records were retrospectively reviewed to identify pressure ulcers. Data were collected by a structured checklist.In ICUs 24 of 90 patients (26.7%, 95% CI: 17.56 to 35.84) that were directly observed and 59 of 310 patients (19.0%, 95% CI: 14.63 to 23.37) that were studied by retrospective review of medical records had pressure ulcers. In medical and surgical wards, 5 of 308 patients (1.6%, 95% CI: 0.20 to 3.00) that were directly observed had pressure ulcers, but no pressure ulcer was detected by review of 600 medical records.Pressure ulcers are significantly more frequent in ICUs than in medical and surgical wards and a significant proportion of pressure ulcers are not reported.